Using Case Study to Analyze the Bilingual Brand Strategy of Barcelona Football Club - Nie, Ning (Transactions on Economics, Business and Management Research, 2024)
Barcelona Football Club is facing the challenge of enhancing its brand influence as globalization deepens. To meet the cultural identity of local fans and the information needs of global fans, Barcelona Football Club has developed a bilingual brand strategy based on Spanish and Catalan. Therefore, the purpose of this study is to explore how Barcelona Football Club uses different brand strategies in a bilingual environment to enhance brand influence and fan loyalty. In the Case Description section, this paper first describes the background, process, and results of Barcelona Football Club’s bilingual brand strategy formation. Then, it analyzes how the strategy specifically enhances brand influence and loyalty from three different perspectives. Finally, corresponding suggestions are provided from these three perspectives. Research has found that the dissemination of bilingual content is one of the factors that enhance Barcelona Football Club’s brand influence. In response to this, it is recommended to better adapt to digital transformation and activate digital media. The implementation of the bilingual marketing strategy has also established a closer connection between Barcelona Football Club and fans. In response to this, Barcelona Football Club should use data-driven insights and achieve personalization. Bilingual cultural adaptation can enhance fan engagement by enriching fan experiences and strengthening cultural identity. Barcelona should strengthen cooperative relationships to increase fan loyalty. This paper holds significance as it offers suggestions for brands to navigate the complex relationship between globalization and localization, while also proposing innovative ideas to enhance their brand influence through language.